2017
DOI: 10.1111/crj.12617
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and distribution of non‐tuberculous mycobacteria isolated from clinical specimens byPCR‐sequencing method inWest ofIran

Abstract: The results of our study showed that the patients were infected by a wide range of atypical mycobacteria. It was concluded that 16S rRNA gene sequencing coupled with rpoB marker is a high discriminatory power in identification of NTM. The presence of various species in clinical samples in Iran emphasizes the use of molecular method like sequence analysis of genes is necessary for reliable identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In the present study, we demonstrated that M. fortuitum , M. abscessus , M. simiae , and M. kansasii are the most common RGM and SGM species in samples of patients from different provinces investigated in this study; this finding is in line with other reports from Iran 17,35,36. Moreover, M. fortuitum was reported as the most common NTM, isolated from environmental and clinical sources in the distinctive part of Iran 37,38…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we demonstrated that M. fortuitum , M. abscessus , M. simiae , and M. kansasii are the most common RGM and SGM species in samples of patients from different provinces investigated in this study; this finding is in line with other reports from Iran 17,35,36. Moreover, M. fortuitum was reported as the most common NTM, isolated from environmental and clinical sources in the distinctive part of Iran 37,38…”
Section: Discussionsupporting
confidence: 92%
“…A study in Iran showed that among 714 positive acid-fast bacilli from TB-suspected cases, 95 isolates were identified as NTM (13.3%) [38]. Furthermore, many NTMPD patients were infected by a wide range of atypical mycobacteria [39]. erefore, it is of great importance to differentiate NTM from Mycobacterium tuberculosis and to make reliable identification in clinical practice to reduce misdiagnosis and improve treatment efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the overall prevalence of NTM diseases has increased globally and is becoming an emerging health issue. The incidence of pulmonary disease caused by NTM is on the rise, 2 , 26 and that of HIV co-infection has also seen a sudden increase. 4 , 5 However, it is difficult to differentiate NTM-caused diseases from MTBC-caused diseases.…”
Section: Discussionmentioning
confidence: 99%